Immunological Effects and Therapeutic Role of C5a in Cancer - Darling, Victoria R. (Expert Rev Clin Immunol, 2014)
The specific role of C5a in cancer, especially in melanoma, has yet to be determined. Differential effects of C5a could be cancer-specific. In the host defense system, C5a functions to protect the body from harmful entities via a plethora of mechanisms. Yet, C5a may also serve to potentiate cancerous process. C5a facilitates cellular proliferation and regeneration by attracting myeloid-derived suppressor cells and supporting tumor promotion. In this article, we critically reviewed the properties, mechanisms of action, and functions of C5a, with particular emphasis on cancer inhibition and promotion, and clinical application of such knowledge in better management of cancer patients. Outstanding questions and future directions in regard to the function of C5a in melanoma and other cancers are discussed.